2008
DOI: 10.1144/0016-76492006-007
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphological evidence for a changing tectonic regime, Pasinler Basin, Turkey

Abstract: Abstract:The Pasinler Basin, in the 'East Anatolian Contractional Province', features a suite of geomorphological zones, visible in the field, air photographs and Landsat and SRTM DEM imagery. These zones reflect past and current tectonically influenced processes.Relicts of the Erzurum-Kars plateau representing Mio-Pliocene volcanism, associated with transtensional tectonics, have been modified by two stages of drainage development: an earlier, shallow valley network, which was modified following uplift and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Such clay can be deposited under high-energy conditions and therefore contains grains of different size. Collins et al (2005Collins et al ( , 2008 have reported such high-energy sedimentation conditions for Pasinler basin. Thus, a significant proportion of the coarse inclusions contained in the Kura-Araxes Ware from Sos Höyük may be of natural origin, embedded within clay bodies as residue from rock weathering.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Such clay can be deposited under high-energy conditions and therefore contains grains of different size. Collins et al (2005Collins et al ( , 2008 have reported such high-energy sedimentation conditions for Pasinler basin. Thus, a significant proportion of the coarse inclusions contained in the Kura-Araxes Ware from Sos Höyük may be of natural origin, embedded within clay bodies as residue from rock weathering.…”
Section: Discussionmentioning
confidence: 88%
“…During the PlioePleistocene, the basin was subject to a compressive tectonic regime and this continues to the present (Ş engör and Kidd, 1979;Ş engör and Yılmaz, 1981;Dewey et al, 1986). Consequently, tilting and subsidence have permitted accumulation of the thick, lacustrine deposits and extensive Pleistocene and Holocene clastic sediments that underlie much of the present basin floor (Collins et al, 2005(Collins et al, , 2008. The main drainage network and various tributaries send terrigenous materials into the Pasinler basin.…”
Section: Geological Settingmentioning
confidence: 99%
“…The sediments comprise fluvial, alluvial fan, and lacustrine deposits (see also Collins et al, 2008;figs. 2 and 4).…”
Section: Methodsmentioning
confidence: 99%
“…The final sedimentary infill comprises Pliocene to Pleistocene lacustrine deposits and extensive Pleistocene to Holocene fluvioterrestrial siliciclastics that directly underlie much of the present-day valley floor (Collins et al, 2005(Collins et al, , 2008 (Figure 1b). These 2 lithological units correspond to the Horasan Beds and Pasinler Beds of Irrlitz (1972), respectively.…”
mentioning
confidence: 99%
“…10a-g and 11h-k, taken from Sengör et al (2008a, b). See for further references to new research, especially on the geomorphology, petrology and geophysics of the High Plateau, Şaroğlu and Yılmaz (1987), Yılmaz et al (1987bYılmaz et al ( , 1998, Şengör et al (2003, 2008), Zor et al (2003Zor et al ( , 2007, Gök et al (2003), Allen et al (2004), Barazangi et al (2006), Bektaş et al (2007), Keskin (2003Keskin ( , 2007, Collins et al (2008), Göğüş and Pysklywec (2008), Türkoğlu et al (2008) and Zor (2008). Only one paper has so far been published disputing the subduction-accretion complex interpretation for the basement of the Eastern Turkish High Plateau (Topuz et al 2017), but that paper presents no evidence whatever to support its rebuttal.…”
Section: Sutures Of the Northern Branch Of The Neo-tethysmentioning
confidence: 99%